Neural Basis of Increased Cognitive Control of Impulsivity During the Mid-Luteal Phase Relative to the Late Follicular Phase of the Menstrual Cycle - Zhuang, Jin-Ying; Wang, Jia-Xi; Lei, Qin; Zhang, Weidong; Fan, Mingxia (Frontiers in Human Neuroscience, 2020)
Hormonal changes across the menstrual cycle have been shown to influence reward-related motivation and impulsive behaviors. Here, to compare neural mechanisms of cognitive impulse control during the mid-luteal phase (LP) versus during the late follicular phase (FP), we employed functional magnetic resonance imaging (fMRI) with an event-related monetary delay discounting (EMDD) behavioral task (study 1) and then employed resting state (RS)-fMRI (study 2). The imaging data were analyzed and related to behavior-associated neural activation. In study 1, women in the late FP showed a preference for sooner rewards while exhibiting enhanced activity in the dorsal striatum (DS), whereas women in the mid-LP showed a preference for delayed, higher-value rewards with enhanced activity in the dorsolateral prefrontal cortex (dlPFC). Discount rate (transformed k) in the EMDD task correlated with functional connectivity (FC) of the DS-dlPFC circuitry, consistent with the possibility that DS-dlPFC circuitry may regulate impulsivity. In study 2, the right dlPFC was significantly more active in mid-LP than in late FP, and this effect was sensitive to estradiol (E2) and relative E2 levels during mid-LP. The magnitude of DS-dlPFC FC correlated negatively with psychometric impulsivity scores during the late FP. These results replicated findings from study 1 and further indicated that relative E2 levels may play an important role in increasing cognitive control during the mid-LP, which provides new insight into the treatment of conditions characterized by hyper-impulsivity, such as obsessive-compulsive disorder, Parkinson disease, and attention deficit hyperactivity disorder. In conclusion, our results suggest that cyclical gonadal hormones affect cognitive control on impulsive behavior periodically, possibility via DS-dlPFC circuitry.